Primary Pulmonary Lymphoma with Superior Vena Cava Syndrome - Alfian Nur Rosyid; Resti Yudhawati Meliana (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Primary Pulmonary Lymphoma (PPL) is a clonal proliferation of lymphoid cells that involve one or two lungs (parenchyma and or bronchi. PPL is found in approximately 0.4% of all lymphoma cases and 3.6% of NHL cases. Five years survival rate at stage I and II is 90%, and 80% in stage III and IV. A 63-year-old male farmer presented with chief complaint of shortness of breath for one week before admission and preceded by coughing for a month, loss of appetite and night sweating. There was an abnormal physical examination on the right side of the chest with non-tender lymph node enlargements in the right supraclavicular and neck region and superior vena cava syndrome. CT guided FNAB suggesting NHL. Patient was treated with CHOP chemotherapy regiment. However, with high grade lymphoma, patient did not respond well.